Effect of N P K S Zn and B on Yield Attributes and Yield of French Bean in South Eastern Hilly Region of Bangladesh - Moniruzzaman, M; Islam, MR; Hasan, H (Journal of Agriculture & Rural Development, 2008)
A field experiment on French bean taking the variety BARI Jhar Shim-2 was conducted with five levels of Nitrogen (0, 40, 80, 120 and 160 kg N ha-1) and four levels of each of phosphorous (0, 40, 80 and 120 kg P2O5 ha-1), potassium (0, 30, 60 and 90 kg K2O ha-1) and sulfur (0, 10, 20 and 30 kg S ha-1), three levels of each of zinc (0, 4 and 8 kg Zn ha-1) and boron (0, 1 and 1.5 kg B ha-1) at the Agricultural Research Station, Raikhali, Rangamati Hill District during Rabi (winter) seasons of 2005-2006 and 2006-2007. The experiment was conducted in Randomized Complete Block Design with three replications. Yield and yield components of French bean were significantly influenced by different fertilizer treatments containing macro and micronutrients separately. Results showed significant effect of fertilizers on plant height, number of branches and leaves per plant, pod length, number of green pods and pod weight per plant and green pod yield during both years. The highest pod yield of 23.14 t ha-1 (average of 2005-2006 and 2006-2007) was obtained with 120-120-60-20-4-1 kg of N-P2O5-K2O-S-Zn-B plus 0.5 kg Mo ha-1 along with 10 tons cowdung per hectare that was closely followed by 120-80-60-20-4-1 kg of N-P2O5-K2O-S-Zn-B plus 0.5 kg Mo ha-1 along with 10 tons cowdung per hectare. The response equations indicated an optimum level of 138.6 kg N, 131.5 kg P2O5, 63.4 kg K2O and 17.4 kg S ha-1 for higher green fruit yield of French bean. The economic doses of nutrients came out to be 135.8-123.3-60-17.4 kg of N-P2O5-K2O-S ha-1. Application of 136-123-60-17-4-1 kg N-P2O5-K2O-S-Zn-B plus 0.5 kg Mo ha-1 along with 10 tons cowdung per hectare might be considered as profitable dose for growing French bean in South-Eastern hilly region of Bangladesh. Key words: Legume, French bean, Rabi, Rangamati, Rhizobium, AEZ-29, physiological maturation. doi:10.3329/jard.v6i1.1660 J Agric Rural Dev 6(1&2), 75-82, June 2008